Repurposing alternative splicing events as potential targets for the design of diagnostic and therapeutic tools in PCa - Martínez-Montiel, Nancy; Vite-Arciniega, José de Jesús; Rosas-Murrieta, Nora Hilda; Martínez-Contreras, Rebeca D. (Frontiers in Oncology, 2025)
Alternative splicing is a key mechanism responsible for protein diversity in eukaryotes. Even when the relevance of this process was initially overlooked, it is now clear that splicing decisions have a strong impact on the physiology of organisms. Moreover, aberrant splicing products have been clearly related to different diseases, including cancer. Deregulation of splicing factors or mutations at the immature mRNA level could be responsible of generating these aberrant products that are involved in cell biology processes, including migration, angiogenesis, differentiation, cell cycle, DNA repair and so on. For this reason, alternative splicing is now considered a hallmark of cancer. Prostate cancer is one of the most frequently diagnosed types of cancer and some of the leading global cause of cancer death men. Prostate cancer shows an important incidence in the developing world, while the mortality rate is growing because of limited medical infrastructure and awareness. Here, we present some of the key alternative splicing events related to prostate cancer and even when the exact role of these isoforms in the development of the disease has not been fully understood, we believe that the correction of these aberrant splicing events represents an attractive target for the design of innovative diagnostic and therapeutic tools.